Long-term preservation of germ cells and gonadal tissues at ambient temperatures - Pierre Comizzoli; Xiaoming He; Pei-Chih Lee (Bioscientifica, 2022)
Objective: To present an overview of different approaches and recent advances for long-term preservation of germ cells and gonadal tissues at ambient temperatures. Methods: Review of the existing literature. Results: Preserving viable spermatozoa, eggs, embryos, and gonadal tissues for the long term is critical in human fertility treatment and for the management of animal populations (livestock, biomedical models, and wild species). The need and number of banked germplasms are growing very fast in all disciplines, but current storage options at freezing temperatures are often constraining and not always sustainable. Recent research indicates that structures and functions of gametes or gonadal tissues can be preserved for the long term using different strategies based on dehydration and storage at supra-zero temperatures. However, more studies are needed in rehydration and reanimation of germplasms (including proper molecular and cellular evaluations). Conclusions: While a lot of research is still warranted to optimize drying and rehydration conditions for each sample type and each species, alternative preservation methods will change the paradigm in fertility preservation and biobanking. It will transform the way we maintain and manage precious biomaterials for the long term.